STUDY OF THE IMPACT OF CLIMATE CHANGE ON PRODUCTIVITY AND DISEASES OF RICE PLANT IN VILLAGES OF SIMALUNGUN DISTRICT - Khairil Hanif; Tri yuslisa sirait; Nurhayati; Asmanizar; Syamsafitri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The aim of the research is to evaluate whether climate change has occurred in Simalungun Regency and study its impact on rice productivity and pest attacks. The research was carried out in March – May 2023 in Simalungun Regency, North Sumatra Province. With the results of the study of the impact of climate change on productivity and disease in rice plants in Sei Merbau village, Ujung Padang subdistrict, Simalungun district, carried out using the location survey method and taking climate data from the BMKG office, data on production, productivity and disease pests on rice plants were taken. from the agricultural service office. The climate data for 3 years that has been obtained is compared each year by looking at the results of developments in productivity and pests and diseases in rice plants in Sei Merbau village, Ujung Padang sub-district, Simalungun district. In 2018-2020, the climate in Simalungun district experienced fluctuations every year which could have an impact on the development of rice plant productivity and rice plant diseases in Simalungun district every year. There is a significant level of correlation between rainfall and rainy days on rice production and productivity in Simalungun Regency.